Pengaruh Penggunaan Media Sosial Dan Inovasi Terhadap Kinerja Umkm Di Provinsi Sumatra Barat Pada Masa Pandemi COVID-19 - Lasmi Yupita (Riset Sinergi Indonesia, 2026)
This study was conducted to see the effect of the use of social media and innovation on the performance of MSMEs in the province of West Sumatra during the Covid-19 pandemic. The research population is SMEs in West Sumatra Province. The sample collection technique is random sampling by distributing questionnaires via google form and directly to MSME actors. Research respondents are 155 SMEs in the province of West Sumatra. Test Analysis of the data used is multiple linear regression. The results of the study indicate that there is a positive and significant influence on the use of social media and innovation on the performance of MSMEs in the province of West Sumatra during the Covid-19 Pandemic Period. From the research that has been done, it can help MSME actors as input to explore the potential of MSMEs in improving performance, by utilizing technology such as maximizing the use of social media and carrying out innovations, especially during the COVID-19 pandemic.